Generalized Anxiety Disorder and Its Associated Factors Among Pregnant Women During COVID-19 at Public Health Facilities of East Gojjam Zone, 2020: A Multi-Center Cross-Sectional Study - Bishaw, Keralem Anteneh; Andalem, Addisu; Amha, Haile; wondie, Tirusew (Frontiers in Global Women's Health, 2022)
Introduction Pregnant women suffer from varying levels of generalized anxiety disorder that result in poor obstetrical outcomes. Therefore, this study aimed to assess the prevalence and factors associated with generalized anxiety disorder among pregnant women attending antenatal care during COVID-19 at the public health facilities in the east Gojjam zone. Methods A health facility-based cross-sectional study was conducted, from 1–30 December 2020. A total of 847 pregnant women were included in the study using a systematic random sampling technique. We used an interviewer-administered questionnaire to collect the data. Bivariate and multivariable logistic regression was used to identify factors associated with the outcome variable. Statistical significance was determined using a p-value < 0.05 and a 95% confidence level. Results The prevalence of generalized anxiety disorder was 43.7%, with a 95% CI (40.28–47.12). Having <3 the number of children (AOR: 1.53; 95% CI: 1.11–2.13, having a negative attitude about COVID (AOR: 1.47; 95% CI: 1.07–2.02 and having a high-risk perception about COVID (AOR: 1.86; 95% CI: 1.34–2.57 were factors significantly associated with generalized anxiety disorder. Conclusions The study found that the prevalence of generalized anxiety disorder was high. Having less than three children, having a negative attitude, and having a high-risk perception of COVID were independent risk factors of generalized anxiety disorder. Appropriate interventions should be considered to address generalized anxiety disorder during the pandemic.